A Rapid Test for Heroin (3,6-Diacetylmorphine) Based on Two Chemiluminescence Reactions - Agg, K.; Craddock, A.; Bos, R.; Francis, P.; Lewis, Simon; Barnett, N. (Blackwell Publishing, 2006)
A rapid method for screening drug seizure samples for 3,6-diacetylmorphine (heroin), which consists of a simple hydrolysis procedure and flow-injection analysis with two chemiluminescence reagents, is described. Before hydrolysis, 3,6-diacetylmorphine evokes an intense response with a tris(2,20-bipyridyl)ruthenium(III) reagent (prepared by dissolving the perchlorate salt in acetonitrile), and a relatively weak chemiluminescence response with a second reagent: potassium permanganate in an aqueous acidic polyphosphate solution. However, the permanganate reagent is extremely sensitive toward the hydrolysis products of 3,6-diacetylmorphine (i.e., 6-monoacetylmorphine and morphine). Some compounds commonly found in drug laboratories may cause false positives with tris(2,20-bipyridyl)ruthenium(III), but do not produce the markedly increased response with the permanganate reagent after the hydrolysis procedure. The combination of these two tests therefore provides an effective presumptive test for the presence of 3,6-diacetylmorphine, which we have verified with 14 samples obtained from a forensic science laboratory.